FLYPAPER EFFECT DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH - Rahmawati, Luluk Atika; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to give empirical evidence whether General Allocation Fund and Local Own-Source Revenue have influence to the local expenditure in sub-districts/cities in East Java Province specifically at the Gerbangkertasusila areas which are i.e.: Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo and Lamongan. And to give empirical evidence whether the flypaper effect occurs in 2009-2013. The population is the area of sub-districts / cities in East Java specifically in the area of Gerbangkertasusila in 2009-2013 periods. Based on the result of test it can be found that simultaneously Local Own-Source Revenue and General Allocation Fund have significant influence to the local expenditure. The coefficient of Local Own Source Revenue is 0.703 and it is significant to the local expenditure compared to the coefficient of General Allocation Fund is 0.273. It also proves that the flypaper effect does not occur in the area with a high Local Own Source Revenue or in a low Local Own Source Revenue.Keywords: Flypaper Effect, General Allocation Fund (DAU), Local Own-Source Revenue, Local Expenditure